2010
DOI: 10.2337/dc10-0031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Interactive Online Nursing Educational Module on Insulin Errors in Hospitalized Pediatric Patients

Abstract: OBJECTIVETo determine the effectiveness of an online module for reducing insulin administration errors by nurses caring for hospitalized pediatric patients.RESEARCH DESIGN AND METHODSPediatric nursing staff completed a mandatory online educational module teaching insulin pharmacokinetics and the insulin order form, using diluted insulin and finishing with 15 interactive cases. A chart audit to determine all possible insulin errors of patients receiving insulin was done before and 2–6 months after the education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
0
19
0
3
Order By: Relevance
“…Although 20 studies reported provider education as part of their intervention to reduce pediatric medication errors, 14 studies 31,34,37,40,56,60,65,71,75,76,78,82,85,87 used education as their main intervention to reduce pediatric medication errors. Seven of these 14 studies collected data for #3 months after implementing the intervention and 2 did not report on the months of systems for all providers.…”
Section: Data Synthesis For Specific Interventionsmentioning
confidence: 99%
“…Although 20 studies reported provider education as part of their intervention to reduce pediatric medication errors, 14 studies 31,34,37,40,56,60,65,71,75,76,78,82,85,87 used education as their main intervention to reduce pediatric medication errors. Seven of these 14 studies collected data for #3 months after implementing the intervention and 2 did not report on the months of systems for all providers.…”
Section: Data Synthesis For Specific Interventionsmentioning
confidence: 99%
“…The six intervention types included: technology (n = 38), organizational (n = 16), [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] personnel (n = 13), [72][73][74][75][76][77][78][79][80][81][82][83][84] pharmacy (n = 9), [85][86][87][88][89][90][91][92][93] hazard and risk analysis (n = 8), 10,[93][94][95][96][97][98][99] and multifactorial (i.e. a combination of any of the previous themes; n = 18).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Development of preformatted medication order sheets [56][57][58][59][60][61][62][63][64] Medication distribution and supply (n = 6) Preparation of prediluted medications for administration [65][66][67][68][69][70] Nurse prescribing (n = 1) Transcription of paper-based orders to electronic orders by nursing staff 71 Personnel (n = 13) Staff education (n = 13) Personalized feedback of medication prescribing errors [72][73][74][75][76][77][78][79][80][81][82][83][84] Pharmacy (n = 9) Ward based (n = 6) Interventions identified through introduction of ward-based paediatric/neonatal clinical pharmacy service [85][86][87][88][89][90] Dispensary based (n = 3) Interventions identified through dispensary-based pharmacy service [91][92][93] Hazard and risk analysis (n = 8) Quality improvement tools (n = 4) Use of failure modes, effects, and criticality analyses to redesign care processes 10,[95][96][97] Error detection tools (n = 3) Automated detection of medication errors 93,…”
Section: Intervention Type Example Of Intervention Referencesmentioning
confidence: 99%
“…Past studies have demonstrated online training to be noninferior to the classroom setting, and an online program signifi cantly decreased errors in insulin administration among pediatric nurses. 29,30 Higher knowledge scores in this study may be specifi c to our Webbased program, which forced residents to engage in embedded quizzes to advance through the case-based modules. Baldwin et al 31 demonstrated that an intense intervention where a staff endocrinologist joined rounds with resident teams twice per day on inpatients with diabetes led to improved inpatient outcomes.…”
Section: Discussionmentioning
confidence: 95%